Efficacy of a one-session fractional picosecond 1064-nm laser for the treatment of atrophic acne scar and enlarged facial pores. (17th November 2021) - Puaratanaarunkon, Thanaporn; Asawanonda, Pravit
ABSTRACT: A picosecond-domain laser reportedly elicits positive treatment outcomes for acne scar and enlarged pores, but multiple sessions are often required. We sought to evaluate the efficacy of one-session fractional picosecond 1064-nm laser in treating atrophic acne scar and conspicuous pores. Fifty-nine acne scar patients with skin phototypes III and IV were treated with picosecond 1064-nm laser with microlens array (MLA) (8 mm spot, 0.8 J/cm 2, 10 Hz) for one session. The efficacy of acne scar was evaluated by Antera® 3D CS, whereas facial pore counts and diameter were evaluated by VISIA-CR and dermoscopic images, respectively. All measurements were performed at baseline, weeks 1, 2, 4 and 6. Acne scar volume and facial pore counts showed a statistically significant reduction at 1 week and subsequent follow-up period when compared to baseline (weeks 1–6; P < .001). The volume of acne scars and the number of enlarge pores decreased by 22.03% and 15.13%, respectively. Of note, there was no significant change in diameter of facial pores. The adverse events, including erythema and folliculitis, were mild and short-lived. A single session of picosecond 1064-nm laser with MLA was safe and effective in improving atrophic acne scar and the number of enlarged pores.